2023
DOI: 10.1002/adhm.202202424
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Reinforcing Nanoplatform for Highly Effective Synergistic Targeted Combinatary Calcium‐Overload and Photodynamic Therapy of Cancer

Abstract: While calcium‐overload‐mediated therapy (COMT) is a promising but largely untapped therapeutic strategy, combinatory therapy greatly boosts treatment outcomes with integrated merits of different therapies. Herein, a BPQD@CaO2‐PEG‐GPC3Ab nanoplatform is formulated by integrating calcium peroxide (CaO2) and black phosphorus quantum dot (BPQD, photosensitizer) with active‐targeting glypican‐3 antibody (GPC3Ab), for combinatory photodynamic therapy (PDT) and COMT in response to acidic pH and near‐infrared (NIR) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…In addition, pH-dependent oxygen release from ACC-CaO 2 was also observed in DMEM probably because ACC on CaO 2 dissolved under weak acidic condition. Although many researchers who used CaO 2 for cancer therapies have mentioned the specific dissolution behavior of CaO 2 in weak acidic cancer environments, the detailed mechanism has not been widely discussed. In this research, we found that CaO 2 easily dissolved even in HEPES with neutral pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pH-dependent oxygen release from ACC-CaO 2 was also observed in DMEM probably because ACC on CaO 2 dissolved under weak acidic condition. Although many researchers who used CaO 2 for cancer therapies have mentioned the specific dissolution behavior of CaO 2 in weak acidic cancer environments, the detailed mechanism has not been widely discussed. In this research, we found that CaO 2 easily dissolved even in HEPES with neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…However, the uncontrollability of oxygen release after immersion in water is an issue, especially for the oxygen-releasing hydrogels. CaO 2 nanoparticles have also recently been used in cancer therapies such as reactive oxygen-species-based chemodynamic therapy, , calcium overload cancer therapy, and photodynamic therapy. Although many researchers have used CaO 2 in cell culture conditions, the nanoscale surface chemistry of CaO 2 in these conditions has not been taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium overload, as the name implies, is the accumulation of free Ca 2+ in the cell cytoplasm resulting in an abnormally high concentration of Ca 2+ , which can lead to severe cellular damage or even cell death [ 93 ]. Normally, calcium signaling acts as a second messenger of cellular signaling to control important physiological processes by modulating the activity of specific targets, which are essentially achieved in response to fluctuations in local calcium concentrations [ 94 ].…”
Section: The Effects and Mechanisms Of Caco 3 Nano...mentioning
confidence: 99%
“…[13] The mechanism of calcification is usually induced by ischemic necrosis of tumor tissue, meaning that the tumor growth is in a quiescent state and there is less risk of distant metastasis. [14] Biological calcification, also named biomineralization, can be accurately modulated by solution medium homeostasis or calcification site selection. [15][16][17][18] If abnormal biomineralization occurs at the tissue surface, this can lead to calcified lesions and accelerated cell death.…”
Section: Introductionmentioning
confidence: 99%